Uses of Plants by the Hidatsas of the Northern Plains. - Wilson, Gilbert Livingston (UNP - Nebraska, 2014)
In 1916 anthropologist Gilbert L. Wilson worked closely with Buffalobird-woman, a highly respected Hidatsa born in 1839 on the Fort Berthold Reservation in western North Dakota, for a study of the Hidatsas' uses of local plants. What resulted was a treasure trove of ethnobotanical information that was buried for more than seventy-five years in Wilson's archives, now held jointly by the Minnesota Historical Society and the American Museum of Natural History in New York City. Wilson recorded Buffalobird-woman's insightful and vivid descriptions of how the nineteenth-century Hidatsa people had.